Regularity for $p$-Harmonic Functions in the Grušin Plane (Journal of Mathematical Study, 2023)
Let $X=\{X_1,X_2\}$ be the orthogonal complement of a Cartan subalgebra in the Grušin plane, whose orthonormal basis is formed by the vector fields $X_1$ and $X_2$. When $1
Keywords: $p$-Laplacian equation; regularities; Grušin plane.